2014
DOI: 10.1016/j.drugalcdep.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The association between changes in alternative reinforcers and short-term smoking cessation

Abstract: Background While more than 50% of smokers make a serious quit attempt each year, less than 10% quit permanently. Evidence from studies of adolescent smoking and other substances of abuse suggest that alternative reinforcers, a construct of Behavioral Economic Theory, may contribute to the likelihood of smoking cessation in adults. This study examined the behavioral economics of smoking cessation within a smoking cessation clinical trial and evaluated how depressive symptoms and behavioral economic variables ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 45 publications
0
27
1
Order By: Relevance
“…This finding is inconsistent with previous analyses of this sample which showed that depressive symptoms were related to cessation outcome 8 weeks of treatment (Goelz et al, 2014). Perhaps depressive symptoms play a more prominent role during the initial weeks of a quit attempt, but are less predictive of long-term cessation outcomes.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding is inconsistent with previous analyses of this sample which showed that depressive symptoms were related to cessation outcome 8 weeks of treatment (Goelz et al, 2014). Perhaps depressive symptoms play a more prominent role during the initial weeks of a quit attempt, but are less predictive of long-term cessation outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…Our earlier study showed that a reduction in complementary reinforcers and an increase in substitute reinforcers predicted short-term (8-week) abstinence (Goelz et al, 2014). Here, we extend that initial finding by showing that substitute environmental reinforcers are associated with long-term abstinence as well and provide support for the continuing investigation of constructs central to behavioral economics as predictors of smoking cessation outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Providing smokers with personalized risk profiles, such as their lung age or heart age (Morris & Temple, 1985; Davies et al, 2013), and training them to imagine positive future events (e.g., Daniel et al, 2013) may help motivate smokers with SMI to seek treatment by increasing the immediacy and salience of the health costs of smoking and the benefits of abstinence. Helping them to identify and engage in substitute reinforcing activities may reduce the likelihood of relapse during cessation treatment by increasing the opportunity cost of smoking (Goelz et al, 2014). …”
Section: Behavioral Economic Approaches To Reducing Smoking In Smimentioning
confidence: 99%